2017
DOI: 10.1021/acs.jafc.7b01876
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Blackberry Press Cake, Polyphenolic Extract, and Defatted Seeds, and Their Effects on Cecal Fermentation, Bacterial Metabolites, and Blood Lipid Profile in Rats

Abstract: Blackberry fiber (BF), extracted blackberry fiber (EBF), defatted blackberry seeds (DBS), and blackberry polyphenols (BP) were added to the diets of rats. A control diet, fiber diets (BF, EBF, DBS) with 6% addition instead of cellulose, and a polyphenol diet (BP) with 1% addition were administered for 4 weeks. BF and DBS contained polyphenols (3.6%); EBF did not. DBS was free of fat. Ellagitannins were the main phenolics, mostly dimers (sanguiin H-6 with isomers) and monomers (pedunculagin, casuarictin isomer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
(121 reference statements)
4
15
0
Order By: Relevance
“…In the present experiment, urolithin A, nasutin A, urolithin A glucuronide, nasutin A glucuronide were detected in the urine of rats treated with the strawberry phenolic fraction, while urolithin A glucuronide, nasutin A glucuronide and DMEAG were found in their blood serum (Tables 4 and 5). It has been reported that in the case of rats the production of nasutin A and its glucuronide was elevated upon the consumption of bis-hexahydroxydiphenoyl--D-glucose (monomeric ET) and agrimoniin (dimeric ET), while dietary EA caused increased concentrations of urolithin A and its glucuronide in the gastrointestinal digesta as well as the inner biological fl uids: blood, lymph, and urine [Jurgoński et al, 2017]. Our results showed that urolithin A and urolithin A glucuronide were present in the urine of rats despite the fact that the phenolic fraction contained only trace amounts of EA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present experiment, urolithin A, nasutin A, urolithin A glucuronide, nasutin A glucuronide were detected in the urine of rats treated with the strawberry phenolic fraction, while urolithin A glucuronide, nasutin A glucuronide and DMEAG were found in their blood serum (Tables 4 and 5). It has been reported that in the case of rats the production of nasutin A and its glucuronide was elevated upon the consumption of bis-hexahydroxydiphenoyl--D-glucose (monomeric ET) and agrimoniin (dimeric ET), while dietary EA caused increased concentrations of urolithin A and its glucuronide in the gastrointestinal digesta as well as the inner biological fl uids: blood, lymph, and urine [Jurgoński et al, 2017]. Our results showed that urolithin A and urolithin A glucuronide were present in the urine of rats despite the fact that the phenolic fraction contained only trace amounts of EA.…”
Section: Resultsmentioning
confidence: 99%
“…Many authors while conducting studies on human volunteers but also on laboratory rodents observed huge differences between individuals within a group in relation to concentrations of ET metabolites [Kosmala et al, 2017; Tomá s-Barberá n et al, 2017]. In the present experiment, the standard error of the mean (SEM) values calculated for each group, and each metabolite were not as high as expected, hence the differences observed between treatments were statistically signifi cant, thus giving the opportunity to observe biological relationships in the ET metabolites formation.…”
Section: Resultsmentioning
confidence: 99%
“…The increased cecal glycoside concentration and secondary metabolites improved glucose consumption ( Table 1 ) [ 290 ]. The increased cecal SCFA concentration suggested an increase in SCFA-producing bacteria; however, the relative abundance of different bacterial groups was not reported [ 130 ]. Blackberry treatment altered the gut microfloral composition by increasing cecal Bacteriodetes over Firmicutes.…”
Section: Blackberriesmentioning
confidence: 99%
“…For this reason, studies on bioactive compounds of poplars focus on the raw material of buds. The supercritical fluid extraction has been widely used in the separation of phenolic compounds from different plant materials (Kosmala et al 2017;Michalak et al 2016;Rój et al 2017). This is evidenced by a number of applications provided by the researchers so far.…”
Section: Poplarmentioning
confidence: 99%